2016
DOI: 10.1016/j.csbj.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Post-Mortem Brain Reveals Changes in Amino Acid and Glucose Metabolism in Mental Illness Compared with Controls

Abstract: Metabolomic profiling was carried out on 53 post-mortem brain samples from subjects diagnosed with schizophrenia, depression, bipolar disorder (SDB), diabetes, and controls. Chromatography on a ZICpHILIC column was used with detection by Orbitrap mass spectrometry. Data extraction was carried out with m/z Mine 2.14 with metabolite searching against an in-house database. There was no clear discrimination between the controls and the SDB samples on the basis of a principal components analysis (PCA) model of 755 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 69 publications
(86 reference statements)
1
21
0
1
Order By: Relevance
“…In addition elevated levels of a pentose were observed in the bipolar brains although not quantified. The elevated level of the pentose mirrored the elevation in the levels pentitols observed in our earlier paper [21].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In addition elevated levels of a pentose were observed in the bipolar brains although not quantified. The elevated level of the pentose mirrored the elevation in the levels pentitols observed in our earlier paper [21].…”
Section: Discussionsupporting
confidence: 80%
“…Unusual sugars do occur in urine and for instance the hexose talose has been observed to be a marker of renal injury [24]. In our earlier paper we showed that post-mortem brains from subjects who had schizophrenia, depression and bipolar disorder had elevated levels of polyols in comparison to controls [21] the details of the samples are given in the earlier paper [21]. Figure 6 shows extracted ion traces for hexoses and pentoses extracted from post-mortem human brain.…”
Section: Profiling Of Sugar Isomers In Urinementioning
confidence: 95%
See 2 more Smart Citations
“…Metabolomics is a growing and powerful technology capable of detecting hundreds to thousands of metabolites in tissues and biofluids [23,24,25,26]. With recent advances in both instrumental and computational metabolomics technologies, it is now possible to gain deeper understanding of the metabolic processes occurring within cancer cells, including how they exploit the process of glycolysis.…”
Section: Introductionmentioning
confidence: 99%